Surface heat transfer due to sliding bubble motion - MURRAY, DARINA (My University, 2009)
The presence of a rising bubble in a fluid can greatly enhance heat transfer from adjacent heated surfaces such as in shell and tube heat exchangers and chemical reactors. One specific case of this is when a bubble impacts and slides along the surface. The result is heat transfer enhancement by two main mechanisms: first, the bubble itself acting as a bluff body, and second, the wake generated behind the bubble leads to increasing mixing. The current research is concerned with measuring the heat transfer from a submerged heated surface that is subject to a sliding bubble flow. An ohmically heated 25 lm thick stainless steel foil, submerged in a water tank, forms the test surface. An air bubble is injected onto the lower surface of the test plate, it slides along its length and the effects are monitored by two methods. Thermochromic liquid crystals (TLC?s) are used in conjunction with a high speed camera to obtain a time varying 2D temperature map of the test surface. A second synchronised camera mounted below the foil records the bubble motion. Tests are performed at angles of 10, 20 and 30 to the horizontal. This paper reports on the enhancement of the heat transfer due to the bubble. It has been found that the angle made between the heated surface and the horizontal influences heat transfer by changing the bubble?s motion. In general, a steeper angle leads to a higher bubble velocity, which results in greater heat transfer enhancement.
PUBLISHED
Keywords: liquid crystals; sliding bubble; heat ransfer enhancement; Smart & Sustainable Planet